2017
DOI: 10.4103/ijccm.ijccm_183_17
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of nebulized heparin for prevention of ventilator induced lung injury: Comparative effects with an inhaled corticosteroid

Abstract: Background:Ventilator-induced lung injury (VILI) is a side effect of mechanical ventilation. Lung inflammation and pulmonary activation of coagulation are induced by mechanical stress. Clinical and preclinical studies show that heparin possesses anti-inflammatory properties. Therefore, we assessed the effects of nebulized heparin in VILI.Methods:Sixty critically ill adult patients who require mechanical ventilation for more than 48 h were included in this prospective, nonrandomized controlled study. Patients r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Based on such results, the research team decided to adjust the treatment protocol to add enoxaparin SC as a prophylaxis against thromboembolic complications and to withhold heparin nebulisation if APTT increased more than double the normal or serious bleeding occurred. Our results correlated well with all the studies done on the nebulized heparin regarding the absence of any bleeding hazards in response to its usage [ 8 , 10 , 14 , 23 25 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Based on such results, the research team decided to adjust the treatment protocol to add enoxaparin SC as a prophylaxis against thromboembolic complications and to withhold heparin nebulisation if APTT increased more than double the normal or serious bleeding occurred. Our results correlated well with all the studies done on the nebulized heparin regarding the absence of any bleeding hazards in response to its usage [ 8 , 10 , 14 , 23 25 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, inhalational heparin has anti-asthmatic properties as confirmed by different clinical models of bronchial asthma [ 8 , 21 ] and inpatients with smoke inhalational injuries [ 8 , 9 , 21 , 22 ]. Heparin nebulization also improved oxygenation and increased the VFDs in critically ill mechanically ventilated patients and was found to be comparable to a nebulized corticosteroid (budesonide) in decreasing the risk of ventilator-induced lung injury [ 14 , 23 ], highlighting its anti-inflammatory effect. Subcutaneous low-molecular-weight heparin also improved the pulmonary functions and decreased the days of MV among AECOPD ventilated patients [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“… 35 37 A pilot study of nebulized UFH for the prevention of ventilator-induced lung injury has been reported. 38 Inhaled prophylactic UFH has also been shown to be effective for the prevention and management of pneumonia and ventilated intensive care unit patients. A phase 1 trial of nebulized heparin in acute lung injury demonstrated better outcomes in heparin-treated groups.…”
Section: Covid-19-associated Viral Coagulopathymentioning
confidence: 99%
“…No convincing benefit of heparin nebulization was found under mechanical ventilation (74) or for prophylaxis for pneumonia patients receiving mechanical ventilation (75,76). In 16 patients with ventilator-induced lung injury, heparin was nebulized proving safety and increasing the number of ventilator-free days (77).…”
Section: Heparinmentioning
confidence: 99%